Vision of the active limb impairs bimanual motor tracking in young and older adults - Boisgontier, Matthieu P.; Van Halewyck, Florian; Corporaal, Sharissa H. A.; Willacker, Lina; Van Den Bergh, Veerle; Beets, Iseult A. M.; Levin, Oron; Swinnen, Stephan P. (Frontiers in Aging Neuroscience, 2014)
Despite the intensive investigation of bimanual coordination, it remains unclear how directing vision toward either limb influences performance, and whether this influence is affected by age. To examine these questions, we assessed the performance of young and older adults on a bimanual tracking task in which they matched motor-driven movements of their right hand (passive limb) with their left hand (active limb) according to in-phase and anti-phase patterns. Performance in six visual conditions involving central vision, and/or peripheral vision of the active and/or passive limb was compared to performance in a no vision condition. Results indicated that directing central vision to the active limb consistently impaired performance, with higher impairment in older than young adults. Conversely, directing central vision to the passive limb improved performance in young adults, but less consistently in older adults. In conditions involving central vision of one limb and peripheral vision of the other limb, similar effects were found to those for conditions involving central vision of one limb only. Peripheral vision alone resulted in similar or impaired performance compared to the no vision condition. These results indicate that the locus of visual attention is critical for bimanual motor control in young and older adults, with older adults being either more impaired or less able to benefit from a given visual condition.